PTH-280 Follow up after colorectal cancer: time to revise the guidance?. (22nd June 2015) - Pearson, K; Pugh, S; Branagan, G; Primrose, J
Abstract : Introduction: Follow-up practice after apparently curative resection for colorectal cancer has until recently been based on limited evidence. ACPGBI guidelines (2007) recommend a single CT during the first two years following resection whereas NICE (2014) advise a more intensive regime with a minimum of two CTs and carcinoembryonic antigen (CEA) measurement at least every six months in first three years. The recent FACS trial now provides us with evidence that that regular follow-up with CEA or CT imaging detects more treatable recurrences than minimal follow-up but that there was no advantage to combining both methods. The DISCLOSE study aimed to assess follow-up practice in seven NHS hospitals. Method: Multi-centre regional audit of patients completing treatment for Dukes' A-C colorectal cancer in 2008. Results: 629 patients were included. Baseline characteristics were comparable to the FACS cohort: 347 (55%) were male, median age 73, 136 (22%) had a Dukes' A primary, 278 (44%) Dukes' B and 215 (34%) Dukes' C. 558 (89%) patients met ACP follow-up guidelines for colorectal cancer. Of the remaining 71 patients, 27 died within two years post original resection and a further five patients declined follow-up. Therefore 590 (94%) patients had appropriate follow up as per ACP recommendations. Exact follow-up regimes did vary between centres and the proportion of patients meeting ACP guidance ranged from 84–99%. Fewer patients, 318 (51%), met current NICE guidelines. Both the overall incidence of recurrence (15.3%) and incidence of surgically treatable recurrence (4.3%) were similar to FACS. Conclusion: The follow-up practices undertaken in this population were successful in achieving comparable incidences of surgically treatable recurrence to the FACS trial. This likely reflects the fact that the majority of patients were followed-up far more intensively than ACP guidance recommends. Whilst only half are compliant with the current recommendations by NICE, the FACS trial suggests that this guidance is too intensive. Neither ACP nor NICE guidance is based on the most up to date evidence and should be revised. Disclosure of interest: None Declared. References: Guidelines for the Management of Colorectal Cancer. 3rd edition (2007). ACPGBI Colorectal cancer (2014) NICE guideline CG131 Primrose JN. Effect of 3 to 5 years of scheduled CEA and CT follow-up to detect recurrence of colorectal cancer: the FACS randomized clinical trial. JAMA. 2014 January 15;311(3):263–70